Simulation of images of CDMAM phantom and the estimation of measurement uncertainties of threshold gold thickness. (July 2017) - Mackenzie, Alistair; Eales, Timothy D; Dunn, Hannah L; Yip Braidley, Mary; Dance, David R.; Young, Kenneth C.
Graphical abstract: Highlights: Using data resampling from 64 images underestimates the CoV of tT by about 13%. ≥16 CDMAM images are required for systems with tT close to the acceptable limit for 0.1 mm disks. The CoVs for disks near the phantom's edge are higher than previously published. The CoV of tT is generally about 4% but can be as high as 12% for 16 images. Abstract: Purpose: To demonstrate a method of simulating mammography images of the CDMAM phantom and to investigate the coefficient of variation (CoV) in the threshold gold thickness ( tT ) measurements associated with use of the phantom. Methods: The noise and sharpness of Hologic Dimensions and GE Essential mammography systems were characterized to provide data for the simulation. The simulation method was validated by comparing the tT results of real and simulated images of the CDMAM phantom for three different doses and the two systems. The detection matrices produced from each of 64 images using CDCOM software were randomly resampled to create 512 sets of 8, 16 and 32 images to estimate the CoV of tT . Sets of simulated images for a range of doses were used to estimate the CoVs for a range of diameters and threshold thicknesses. Results: No significant differences were found for tT or the CoV between real and simulated CDMAM images. It was shown that resampling from 256 images was required for estimating the CoV. The CoV was around 4% using 16 images for most of the phantom but is over double that for details near the edge of the phantom. Conclusions: We have demonstrated a method to simulate images of the CDMAM phantom for different systems at a range of doses. We provide data for calculating uncertainties in tT . Any future review of the European guidelines should take into consideration the calculated uncertainties for the 0.1 mm detail.